From Code to Weakly Hard Constraints: A Pragmatic End-to-End Toolchain for Timed C - Natarajan, Saranya (2020)
RTSS 2019 originally postponed from December 2019 (Hong-Kong) to February 2020 (York, UK) was cancelled.